Text as Image: A Case Study of the Lithuanian Translation of Art Spiegelman’s Graphic Novel MAUS - Pekūnas, Žygimantas (Vertimo studijos, 2019)
This article contributes to the multimodal investigation of comics translation, a highly semiotic activity. The author discusses the visual representation of the text as an image through a case study of the Lithuanian translation of Art Spiegelman’s graphic novel MAUS (translated into Lithuanian by Juškienė and Lempert, 2012). While viewing multimodality as a translation tool and a challenging area, he claims that the visual representation of the text is an integral part of the original multimodal event, whereby the meaning is conveyed through an intrinsic relationship between verbal and non-verbal elements, and that any distortion of those would result in alterations or losses in meaning. The results demonstrated that indeed even the smallest alterations of the visual representation of the text produced shifts in meaning; most of those shifts were pragmatic ambiguities, however, in certain instances there was a loss of semantic emphasis or narrative production. Comics translators and publishers are thus urged to fully comprehend the very dynamic and complex nature of multimodal texts and make every effort to ensure that translation would not result in any multimodal disruptions, if such preservation is technologically available.
Keywords: translation; comics; multimodality; MAUS